Study on Content of Nitrogen, Phosphorus, and Potassium from Mixed Waste of Empty Fruit Bunch of Oil Palm and Banana Stem as Organic Fertilizer for Tomato Plants - Akram La Kilo; Sarmini A Iladat; Hendri Iyabu (Indonesian Journal of Chemistry and Environment, 2023)
The purpose of this research was to study the levels of nitrogen, phosphorus, and potassium (NPK) contained in organic fertilizer made from a mixture of empty fruit bunch waste from oil palm and banana stems, as well as to determine the effects on the growth and development of tomato plants when applying the organic fertilizer made from the aforementioned mixture. The research involved analyzing the total nitrogen content using the Kjeldahl method, phosphorus (P) using UV-VIS, and potassium (K) using AAS, as well as conducting tomato planting experiments using a growing medium consisting of compost made from the mixture of empty fruit bunch waste from oil palm and banana stems. Based on the research results, it was found that the NPK content of the soil and compost mixture of empty fruit bunch waste from oil palm and banana stems met the SNI 19-7030-2004 standard for nitrogen (N) and phosphorus (P). The growth and development of tomato plants without using the organic fertilizer mixture from the mixture of empty fruit bunch waste from oil palm and banana stems underwent some changes, but the changes occurred at a slower pace compared to using the organic fertilizer mixture from the aforementioned mixture.